2018
DOI: 10.1016/j.dsr2.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Living (stained) deep-sea foraminifera from the Sea of Marmara: A preliminary study

Abstract: In this preliminary study, we investigate living (stained) foraminifera from the Sea of Marmara. We focus on the faunal composition and geochemical signatures (trace elements, carbon and oxygen stable isotopes) in foraminiferal tests at two deep-sea sites (329 and~1240 m depth respectively). Documented by ROV observations and sampling, both study areas are heterogeneous (including bacterial mats and carbonate concretions), proximal to cold seeps and consist of dysoxic bottom water (O 2 < 20 µmol/L). The prevai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 117 publications
(190 reference statements)
0
8
0
Order By: Relevance
“…It has been shown that the gas bubbles emitted at the seafloor are mixtures of primary and secondary microbial gases with thermogenic and mantlederived gases with very asymmetric contribution of each source (Ruffine et al, 2018a). The sediments in the vicinity of the seeps host living benthic Foraminifera, and a study from samples collected on the Central High and the Çınarcık Basin show that Bolivina vadescens and Globobulimina affinis are the two dominant species at the study areas (Fontanier et al, 2018). Three articles (Akhoudas et al, 2018;Çağatay et al, 2018;Teichert et al, 2018) deal specifically with the texture, mineralogical and isotopic compositions and genesis of authigenic carbonate crusts associated with cold seeps in the SoM.…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that the gas bubbles emitted at the seafloor are mixtures of primary and secondary microbial gases with thermogenic and mantlederived gases with very asymmetric contribution of each source (Ruffine et al, 2018a). The sediments in the vicinity of the seeps host living benthic Foraminifera, and a study from samples collected on the Central High and the Çınarcık Basin show that Bolivina vadescens and Globobulimina affinis are the two dominant species at the study areas (Fontanier et al, 2018). Three articles (Akhoudas et al, 2018;Çağatay et al, 2018;Teichert et al, 2018) deal specifically with the texture, mineralogical and isotopic compositions and genesis of authigenic carbonate crusts associated with cold seeps in the SoM.…”
Section: Introductionmentioning
confidence: 96%
“…Relationship between Mg/Ca and Sr/Ca (mol ratio) in seafloor authigenic carbonate crusts (Çağatay et al, ), benthic foraminifera (Fontanier et al, ), and bulk carbonate in sediments from the Marmara Sea (this study). The dashed lines correspond to mixing lines between hypothetical end‐members: terrigenous material, aragonite, Mg‐calcite, and biogenic calcite.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of biogenic, authigenic, and detrital carbonates to bulk carbonates were investigated with a mixing model in which four end member ratios of Sr/Ca and Mg/Ca were used (Bayon et al, ; Çağatay et al, ; Fontanier et al, ; Figure ). The results from MRS‐CS‐16 follow a mixing line between detrital calcite and biogenic calcite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg concentrations were calculated using masses 24 and 26; Sr concentrations were calculated with mass 88. One big advantage in using LA-ICP-MS measurements is that single laser pulses remove only a few nanometers of material, which allows high-resolution trace element profiles to be acquired (e.g., Reichart et al, 2003;Regenberg et al, 2006;Dueñas-Bohórquez et al, 2009Hathorne et al, 2009;Munsel et al, 2010;Dissard et al, , 2010aEvans et al, 2013Evans et al, , 2015Steinhardt, 2014Steinhardt, , 2015Fehrenbacher et al, 2015;Langer et al, 2016;Koho et al, 2015Koho et al, , 2017Fontanier et al, 2018;de Nooijer et al, 2007de Nooijer et al, , 2014de Nooijer et al, , 2017aJentzen et al, 2018;Schmitt et al, 2019;Levi et al, 2019). Element concentrations were calculated for the individual ablation profiles integrating the different isotopes (glitter software).…”
Section: Elemental Composition Analysismentioning
confidence: 99%